Effect of hot extrusion parameters on microhardness and microstructure in direct recycling of aluminium chips [Einfluss von Warmstrangpress-Parametern auf die Mikrohärte und das Gefüge beim Wiederverwerten von Aluminiumspänen] - Rady, Mohammed Hussien; Mustapa, Mohammad Sukri; Harimon, Mohd Azhar; Ibrahim, Mustaffa R.; Shamsudin, S.; Lajis, Mohd Amri; Wagiman, Abdullah; Msebawi, Muntadher S.; Yusof, Farazila (Wiley-VCH Verlag, 2019)
Direct hot extrusion is an alternative process for recycling aluminium without melting the scrap. It utilizes low energy and is environmental friendly. This paper reports the microhardness and microstructure of aluminium alloy chips when subjected to various settings of preheating temperature and preheating time in hot extrusion process. Three values of preheating temperature are taken as 450 °C, 500 °C, and 550 °C. On the other hand, three values of preheating time were chosen (1 h, 2 h, 3 h). The influences of the process parameters (preheating temperature and time) are analyzed using design of experiments approach whereby full factorial design with center point analysis are adopted. The total runs are 11 and they comprise of two factors of full factorial design with 3 center points. The responses are microhardness and microstructure. The results show that microhardness increases with the decrease of the preheating temperature. The results also show that the preheating temperature is more important to be controlled rather than the preheating time in microhardness analyses. The profile extrudes at 450 °C and 1 hour has gained the optimum microhardness and it can be concluded that setting temperature at 550 °C for 3 hours results in the highest responses for average grain sizes in analysis of microstructure. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim